2011
DOI: 10.1017/jfm.2011.70
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a translating plunging jet on a pool of the same liquid

Abstract: An experimental study on the impact of a translating two-dimensional transient jet on an initially quiescent liquid pool is studied experimentally using high-speed cinematic visualization and particle image velocimetry methods. Six jet conditions (covering a range of jet thicknesses, velocities and inclination angles relative to vertical) are considered, with measurements performed over a range of horizontal translation speeds for each jet condition. For all conditions studied herein, the jet penetrates into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Gomez-Ledesma, Kiger & Duncan (2011) presented an experimental study on the impact of a translating 2D transient jet on an initially quiescent liquid pool, mimicking a plunging breaker situation. The Reynolds numbers ranged between 6520 and 9754, whereas the Weber numbers considered were between 2.1 and 4.6.…”
Section: Scale Effects and Mesh Grid Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Gomez-Ledesma, Kiger & Duncan (2011) presented an experimental study on the impact of a translating 2D transient jet on an initially quiescent liquid pool, mimicking a plunging breaker situation. The Reynolds numbers ranged between 6520 and 9754, whereas the Weber numbers considered were between 2.1 and 4.6.…”
Section: Scale Effects and Mesh Grid Sensitivitymentioning
confidence: 99%
“…The jets were shown to penetrate into the pool, producing clouds of bubbles, entrained downstream and eventually observed to rise under the influence of buoyancy. Gomez-Ledesma et al (2011) indicated that higher translation speeds would have generated non-penetrating jet impacts, allowing the creation of larger upstream splash-ups as in a plunging breaker (Kiger & Duncan 2012). We also considered the same Reynolds number (Re j ) with respect to the subsequent plunging jet about to impact the forward face of the wave, leading to the generation of vortex filaments.…”
Section: Scale Effects and Mesh Grid Sensitivitymentioning
confidence: 99%
“…Chanson et al [7] mainly focused on the air entrainment characteristics after cavity disintegration, indicating that the maximum air concentration decreased exponentially with the axial distance from the impact point, and obtained an empirical expression for predicting the air entrainment concentration distribution in the pool. For inclined jets, Gómez-Ledesma et al [8] conducted experimental research on a two-dimensional plunging jet into a pool translating at a constant speed. In their study, the jet thickness, speed, and angle relative to vertical were variables.…”
mentioning
confidence: 99%
“…All the above studies were simulations of vertical circular jets. For inclined plunging jets, Brouilliot and Lubin [21] took the experiments of Gómez-Ledesma et al [8] as a prototype and used the LES two-dimensional numerical method to simulate this process. eir results showed that the calculated values were in good agreement with the experimental results.…”
mentioning
confidence: 99%